2016
DOI: 10.1016/j.biortech.2016.03.102
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive techno-economic analysis of wastewater-based algal biofuel production: A case study

Abstract: Combining algae cultivation and wastewater treatment for biofuel production is considered the feasible way for resource utilization. An updated comprehensive techno-economic analysis method that integrates resources availability into techno-economic analysis was employed to evaluate the wastewater-based algal biofuel production with the consideration of wastewater treatment improvement, greenhouse gases emissions, biofuel production costs, and coproduct utilization. An innovative approach consisting of microal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(58 citation statements)
references
References 32 publications
0
53
2
3
Order By: Relevance
“…Therefore, combining microalgae cultivation and wastewater treatment for biofuel production is currently considered a pathway for resource utilization/waste to profit. [ 86 ] In this sense, the cost of biofuel production can be substantially reduced and a biodiesel cost of US$2.23 per gallon (i.e., 52.83 Cents L −1 ) has been estimated under this scenario. [ 86 ] Other high‐value bioproducts co‐produced with biofuel could generate several billions of dollars annually ( Figure 6 ).…”
Section: Feasibility Of Microalgae‐based Wastewater Treatment In Devementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, combining microalgae cultivation and wastewater treatment for biofuel production is currently considered a pathway for resource utilization/waste to profit. [ 86 ] In this sense, the cost of biofuel production can be substantially reduced and a biodiesel cost of US$2.23 per gallon (i.e., 52.83 Cents L −1 ) has been estimated under this scenario. [ 86 ] Other high‐value bioproducts co‐produced with biofuel could generate several billions of dollars annually ( Figure 6 ).…”
Section: Feasibility Of Microalgae‐based Wastewater Treatment In Devementioning
confidence: 99%
“…[ 86 ] In this sense, the cost of biofuel production can be substantially reduced and a biodiesel cost of US$2.23 per gallon (i.e., 52.83 Cents L −1 ) has been estimated under this scenario. [ 86 ] Other high‐value bioproducts co‐produced with biofuel could generate several billions of dollars annually ( Figure 6 ). Therefore, installation of microalgae‐based wastewater treatment in African countries would be economically feasible, creates employment and support economic growth.…”
Section: Feasibility Of Microalgae‐based Wastewater Treatment In Devementioning
confidence: 99%
“…We review the application of T. varibilis in bioenergy production from the perspective of liquid (biodiesel, bioethanol) and gaseous (biohydrogen, biomethane) biofuels. Applying microalgae systems for bioenergy production has several environmental advantages, such as reduction of pollutant emissions and soil erosion, and economic benefits such as tax credits and grants without competing with agricultural produce for freshwater and arable land . In addition to these general advantages, T. variabilis has enhanced capacity for auto‐flocculation, which is one of the most important characteristics to decrease energy consumption during algae biomass harvesting.…”
Section: Bioenergy Production Using T Variabilismentioning
confidence: 99%
“…However, several research groups have demonstrated that under certain circumstances, large‐scale H 2 ‐photo production using microalgae is viable . Previously, scaling up the algal systems for bioenergy production was investigated from different techno‐economic and socio‐environmental angles considering various parameters, such as water and energy consumption, cultivation and harvesting technologies, and associated costs and savings . Open raceway ponds with lower capital and operational costs, in comparison to PBRs, represent an attractive option for commercial large‐scale bioenergy production .…”
Section: Bioenergy Production Using T Variabilismentioning
confidence: 99%
“…The to tal car bon cred its were the sum of car bon re moval cred its mi nus car bon emis sions dur ing waste-based biofuel pro duc tion [15]. The sav ing of sludge dis posal was not con sid ered because there was no sig nif i cant re duc tion on the sludge dis posal be tween in cin er a tion and py rol y sis.…”
Section: Pa Ram E Ters Es Ti Ma Tion Meth Ods -Rev E Nue Es Ti Ma Tionmentioning
confidence: 99%